2012
DOI: 10.4103/2224-3151.207021
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with knowledge about breastfeeding among female garment workers in Dhaka city

Abstract: A large proportion of female garment workers had inadequate knowledge regarding breastfeeding. It is also important that health education on breastfeeding is urgently provided to the female garments workers of Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
6
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 2 publications
4
24
6
4
Order By: Relevance
“…Media can play a pivotal role in enhancing the knowledge of breastfeeding in the target population. A study done in Dhaka [17] showed that majority had knowledge on duration of exclusive breastfeeding (74%) and breastfeeding (66%) and this finding was in coherence with our study which showed that more than 70% (n=134) agreed to the fact that exclusive breast feeding should be given for six month and 79.6% (n=148) knew that complementary feed should be started after six months. A cross sectional study done in Puducherry [8] concluded that the knowledge of mothers was inadequate in areas of initiation of breast feeding (95%), colostrum feeding (56%), exclusive breast feeding (38%) which was discordant with the findings of our study.…”
Section: Discussionsupporting
confidence: 79%
“…Media can play a pivotal role in enhancing the knowledge of breastfeeding in the target population. A study done in Dhaka [17] showed that majority had knowledge on duration of exclusive breastfeeding (74%) and breastfeeding (66%) and this finding was in coherence with our study which showed that more than 70% (n=134) agreed to the fact that exclusive breast feeding should be given for six month and 79.6% (n=148) knew that complementary feed should be started after six months. A cross sectional study done in Puducherry [8] concluded that the knowledge of mothers was inadequate in areas of initiation of breast feeding (95%), colostrum feeding (56%), exclusive breast feeding (38%) which was discordant with the findings of our study.…”
Section: Discussionsupporting
confidence: 79%
“…A scoring system was developed for each component: each correct answer was given a score of one, a score of 0 for wrong answers and for multiple choice question answers a score of one was given for each correct answer. 20 Total score was computed by adding all the individual scores, and score in terms of percentage were calculated. Questionnaire was pretested among 10% of the total sample and those participants included in pretest were excluded from the main study.…”
Section: Methodsmentioning
confidence: 99%
“…8 Sama halnya dengan penelitian yang dilakukan di Dhaka. 9 ASI makanan yang sempurna bagi bayi, namun dewasa ini banyak faktor yang menghambat pemberian ASI ekslusif kepada bayi, diantaranya budaya pemberian makanan pralaktal, pemberian susu formula karena ASI tidak keluar, dan ibu ingin mencoba pemberian susu formula karena harus meninggalkan anak untuk bekerja. 10 Hasil penelitian di Ghana menyatakan ibu yang bekerja mengaku sulit menyusui bayinya secara eksklusif.…”
Section: Pendahuluanunclassified